2008
DOI: 10.1099/vir.0.2008/004051-0
|View full text |Cite
|
Sign up to set email alerts
|

Human metapneumovirus nucleoprotein and phosphoprotein interact and provide the minimal requirements for inclusion body formation

Abstract: Human metapneumovirus (HMPV) is a recently discovered paramyxovirus of the subfamily Pneumovirinae, which also includes avian pneumovirus and human respiratory syncytial virus (HRSV). HMPV is an important cause of respiratory disease worldwide. To understand early events in HMPV replication, cDNAs encoding the HMPV nucleoprotein (N), phosphoprotein (P), matrix protein (M), M2-1 protein and M2-2 protein were cloned from cells infected with the genotype A1 HMPV wild-type strain TN/96-12. HMPV N and P were shown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
52
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 43 publications
2
52
4
Order By: Relevance
“…This indicates that the minimum requirement for the formation of inclusion bodies is interaction of RNA-N with P, not N 0 with P. So far, studies of inclusion bodies of NNS RNA viruses have been extensively reported. Derdowski et al (55) showed that in a recently discovered paramyxovirus, human metapneumovirus, N and P proteins provide the minimal viral requirements for cytoplasmic inclusion body formation in the absence of viral infection. Respiratory syncytial virus forms cytoplasmic inclusion bodies that contain viral RNA, N, and P and the viral polymerase complex and are thought to be sites of nucleocapsid accumulation and viral RNA synthesis (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the minimum requirement for the formation of inclusion bodies is interaction of RNA-N with P, not N 0 with P. So far, studies of inclusion bodies of NNS RNA viruses have been extensively reported. Derdowski et al (55) showed that in a recently discovered paramyxovirus, human metapneumovirus, N and P proteins provide the minimal viral requirements for cytoplasmic inclusion body formation in the absence of viral infection. Respiratory syncytial virus forms cytoplasmic inclusion bodies that contain viral RNA, N, and P and the viral polymerase complex and are thought to be sites of nucleocapsid accumulation and viral RNA synthesis (46,47).…”
Section: Discussionmentioning
confidence: 99%
“…RSV forms cytoplasmic inclusion bodies (IBs) during infection, as also has been reported for measles virus and human metapneumovirus, also of the family Paramyxoviridae (3)(4)(5). In the case of RSV, the IBs have been shown to contain the RSV nucleoprotein (N), phosphoprotein (P), M2-1 protein, and large polymerase (L) protein (4,6).…”
mentioning
confidence: 91%
“…The genome is encapsidated by multiple copies of the nucleoprotein (N) to give rise to helical nucleocapsids (7). Additionally, copies of the phosphoprotein (P) interact with N and recruit the L protein, an RNA-dependent RNA polymerase, and the cofactor M2-1 to the viral nucleocapsids (8)(9)(10)(11). Estimates for Sendai virus, a paramyxovirus, show that a virion can contain up to 2,600 copies of N, 300 copies of P, and 50 copies of the L protein (12).…”
mentioning
confidence: 99%
“…Nucleocapsids were found within these non-membrane-bound bodies, and therefore, they were proposed to be viral replicative sites. For members of the Pneumoviridae, inclusion body formation upon infection or coexpression of the N and P proteins has been reported (8,29,30).…”
mentioning
confidence: 99%